Racial and historical considerations of Benny Goodman’s 1956 state-sponsored tour of Southeast Asia - Slage-Koch, Denin (Jazz Research Journal, 2023)
The state-sponsored jazz diplomacy tours of the 1950s and 1960s have generally been well-documented, but Benny Goodman’s 1956 tour of Southeast Asia remains relatively under-researched. Considering the United States’ heavy military and surveillance interests in the region at the time, Goodman’s tour merits further consideration as a key element of diplomacy during the early stages of the conflict in Vietnam. In particular, Goodman’s tour, while effective, highlights American racial hypocrisy at the beginning of the Civil Rights movement in the mid-1950s. Despite this, Goodman’s efforts contributed significantly to US-Thai relations, which ultimately became one of the most important alliances of the Vietnam War.